Prediction of diuretic response to tolvaptan by a simple, readily available spot urine Na/K ratio - Komiyama, Yasuyuki (PLoS One, 2017)
BACKGROUND: Tolvaptan is vasopressin type 2 receptor antagonist that inhibits water reabsorption. It is used in combination with standard diuretics to treat ascites unresponsive to standard diuretic therapy or hyponatremia because of liver cirrhosis. This study evaluated the effectiveness and safety of tolvaptan in clinical practice and aimed to determine the factors related to its effectiveness. METHODS: Tolvaptan was administered to 88 consecutive cirrhotic patients with ascites unresponsive to standard diuretic therapy. An effective treatment response was a ≥2% reduction in body weight on day 7. The association of patient pretreatment characteristics with therapeutic effects was analyzed. RESULTS: Mean weight reduction on day 7 of tolvaptan therapy was −2.9% ± 3.2%, and treatment was effective in 52% of patients. Multivariate analysis revealed that spot urine Na/K ratio ≥2.5 at baseline was the only factor independently related to therapeutic effect, with an odds ratio of 7.85 (95% confidence interval 2.64–23.40, p = 0.0002). Weight reduction percentage on day 7 was −4.0% ± 2.8% in patients with spot urine Na/K ≥2.5, which was significantly greater than the 0.7% ± 2.7% loss in those with urine Na/K < 2.5 (p < 0.05). A spot urine Na/K ratio ≥2.5 had a sensitivity of 85% and specificity of 60% for predicting effective treatment. No adverse events of treatment led to treatment discontinuation. CONCLUSIONS: Baseline spot urine Na/K was predictive of an effective response to tolvaptan therapy. It is simple to perform and readily available and might serve as an indicator of optimal timing of tolvaptan administration in patients with inadequate response to conventional Na diuretic therapy.